2002
DOI: 10.1073/pnas.102019899
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of mitochondrial protein synthesis results in increased endothelial cell susceptibility to nitric oxide-induced apoptosis

Abstract: Mutations in mitochondrial DNA, affecting the activity of respiratory complexes, have been implicated in many chronic degenerative diseases. Mitochondrial proteins coded for by both the mitochondrial and nuclear genes are known to have important signaling roles in apoptosis. However, the impact of the inhibition of mitochondrial protein synthesis on apoptosis is largely unknown. This inhibition is particularly important in NO-dependent cytotoxicity, which is believed to have a significant mitochondrial compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 41 publications
4
35
0
2
Order By: Relevance
“…We found that CAP did not significantly affect ATP levels in the neurons (Fig. 5C), consistent with the lack of effect of CAP treatment for up to 55 h on ATP levels in other cell types in culture (37). To examine the effect of CAP on mitochondrial membrane potential (⌬ M ), we monitored the dequenching of tetramethylrhodamine methyl ester fluorescence evoked by bath applying the mitochondrial uncoupler carbonyl cyanide p-trifluoromethoxyphenylhydrazone (38) in individual neurons from CAP-treated or control cultures.…”
Section: Loss Of Nd2 In Neurons Prevents the Regulation Of Nmda Receptorsupporting
confidence: 69%
“…We found that CAP did not significantly affect ATP levels in the neurons (Fig. 5C), consistent with the lack of effect of CAP treatment for up to 55 h on ATP levels in other cell types in culture (37). To examine the effect of CAP on mitochondrial membrane potential (⌬ M ), we monitored the dequenching of tetramethylrhodamine methyl ester fluorescence evoked by bath applying the mitochondrial uncoupler carbonyl cyanide p-trifluoromethoxyphenylhydrazone (38) in individual neurons from CAP-treated or control cultures.…”
Section: Loss Of Nd2 In Neurons Prevents the Regulation Of Nmda Receptorsupporting
confidence: 69%
“…mtDNA is responsible for the synthesis of 13 subunits of mitochondrial electron transport chain (Anderson et al, 1981). Because turnover of mitochondrial proteins occurs independently (Ramachandran et al, 2002), imbalance and/or impairment of the electron transport system caused by mtDNA injury may facilitate leakage of electrons to generate the superoxide radical (Han et al, 2001). Although rotenone (50 M) and antimycin (50 M) instantaneously increase mitochondrial ROS (data not shown), its generation induced by the agents interacting with DNA increased fairly slowly (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2A-C). Both TNF-␣ (a cytokine shown to reduce mitochondrial biogenesis and increase susceptibility to mitochondrial injury [18,19]) and chloramphenicol (a specific inhibitor of mitochondrial protein synthesis [20]) reduced adiponectin synthesis and mtDNA content (Fig. 2F and G).…”
Section: Resultsmentioning
confidence: 99%
“…The db/db mice were treated for 4 weeks with 20 (13). Oxygen comsumption in epididymal adipose tissue was measured using a 782 single-dual-channel oxygen meter (Strathkelvin Instruments, Glasgow, U.K.).…”
Section: Methodsmentioning
confidence: 99%